Squamous metaplasia amplifies pathologic epithelial-mesenchymal interactions in COPD patients - Araya, Jun (American Society for Clinical Investigation, 2007)
Squamous metaplasia (SM) is common in smokers and is associated with airway obstruction in chronic obstructive pulmonary disease (COPD). A major mechanism of airway obstruction in COPD is thickening of the small airway walls. We asked whether SM actively contributes to airway wall thickening through alteration of epithelial-mesenchymal interactions in COPD. Using immunohistochemical staining, airway morphometry, and fibroblast culture of lung samples from COPD patients; genome-wide analysis of an in vitro model of SM; and in vitro modeling of human airway epithelial-mesenchymal interactions, we provide evidence that SM, through the increased secretion of IL-1β, induces a fibrotic response in adjacent airway fibroblasts. We identify a pivotal role for integrin-mediated TGF-β activation in amplifying SM and driving IL-1β–dependent profibrotic mesenchymal responses. Finally, we show that SM correlates with increased severity of COPD and that fibroblast expression of the integrin α(v)β(8), which is the major mediator of airway fibroblast TGF-β activation, correlated with disease severity and small airway wall thickening in COPD. Our findings have identified TGF-β as a potential therapeutic target for COPD.